Long‐term follow‐up of adult patients with congenital heart disease and an implantable cardioverter defibrillator. (19th March 2019) - Coutinho Cruz, Madalena; Viveiros Monteiro, André; Portugal, Guilherme; Laranjo, Sérgio; Lousinha, Ana; Valente, Bruno; Osório, Paulo; Silva Cunha, Pedro; de Sousa, Lídia; Oliveira, José Alberto; Agapito, Ana; Martins Oliveira, Mário; et al.
Abstract: Objective: Sudden cardiac death is common in the adult congenital heart disease (ACHD) population. Knowledge and experience about the use of implantable cardioverter defibrillators (ICD) in ACHD patients is very limited. We aimed to characterize a cohort of patients with ACHD and ICDs. Design: Thirty consecutive ACHD patients submitted to an ICD implantation in a single tertiary center were evaluated. Data on baseline clinical features, heart defect, indication for ICD, type of device, appropriate therapies, ICD‐related complication, and mortality during follow‐up were collected. Results: Of the 30 patients,  56.7% received appropriate therapies due to ventricular tachycardia (VT) or ventricular fibrillation (VF). The rate of inappropriate therapies and device‐related complications was 33.3%. Secondary prevention and primary prevention patients with class I indications for ICD had more appropriate therapies than complication, but this relationship was reversed for patients with class II indications. Remote monitoring played an important role in diagnosing new atrial arrhythmias before scheduled visits in 46.2% of patients, leading to a change in medication. VT/VF episodes were associated with a composite of death, cardiac transplantation, and hospital admission (OR 13.0; 95% CI: 2.1‐81.5). Conclusion: ICDs are not only useful in preventing SCD, but also have a major role in diagnosing atrial tachyarrhythmias ahead of scheduled visits. Although improvements in ICD technology might reduce complications and inappropriate therapies, adequate selection of candidates for primary prevention still remains difficult because of the lack of clear indications.